Hubungan Antara Gaya Belajar Dengan Kemampuan Kognitif Matematika Pada Materi Lingkaran di SMP Negeri 2 Limboto - Une, Dewi Fatmawaty; Hulukati, Evi; Ismail, Yamin; Abdullah, Abdul Wahab; Usman, Kartin (Research in the Mathematical and Natural Sciences, 2022)
This research is survey research using correlation techniques whics aims to determine the correlation between learning styles and cognitive ability on circle material. This research was conducted at grade VIII students of Junior High School SMP Negeri 2 Limboto, Gorontalo regency, 2017/2018 academic year with a sample of 119 students. Data collection techniques were carried out using questionnaires and test. The questionnaire is to obtain learning style data, while the test is to obtain students’ cognitive ability data on circle material. Further, the hypothesis is tested using regression and correlation analysis. Based on the results of data analysis, it is shown that there was a positive correlation between learning styles and cognitive ability on circle material at grade VIII of Junior High School SMP Negeri 2 Limboto, Gorontalo regency. The contribution of learning styles given to students’ cognitive ability on circle material is 9.14%. This value shows the influence given by the learning style of students’ cognitive ability. The result provides information that the lack of selecting and understanding of each student’s learning style influences the level of cognitive abilities, especially on circle material even though the contribution is given is 9.14%.